Exploring the Effects of Greek Yogurt Supplementation and Exercise Training on Serum Lithium and Its Relationship With Musculoskeletal Outcomes in Men - Baranowski, Ryan W.; Skelly, Lauren E.; Josse, Andrea R.; Fajardo, Val A. (Frontiers in Nutrition, 2021)
Dairy products can act as a dietary source of lithium (Li), and a recent study in university-aged males demonstrated that Greek yogurt (GY) supplementation augmented gains in fat free mass, strength and bone formation after 12 weeks of resistance exercise training compared to carbohydrate (CHO) pudding supplementation. Here in this brief research report, we performed secondary analyses to explore whether GY would alter serum Li levels and whether changes in serum Li would associate with changes in body composition, strength, and bone turnover markers. Our results show that the GY group maintained serum Li levels after exercise training, whereas the CHO group did not. Furthermore, maintaining/elevating serum Li levels was also associated with greater gains in strength and reductions in bone resorption. Thus, future studies should assess the potential causative role of dietary Li on strength and bone resorption in humans.